Utilizing steric bulk to stabilize molybdenum aminogermylyne and aminogermylene complexes - Hicks, Jamie; Schenk, Christian (Organometallics, 2013)
Two extremely bulky bis(aryl)amines, HN(Ar*)(Ph) (HLPh) and HN(Ar*)(Mes) (HLMes) (Ar* = C6H2{C(H)Ph2}2Me-2,6,4; Mes = mesityl), have been prepared by palladium-catalyzed cross-coupling reactions and structurally characterized. These have been utilized in the preparation of the amido-germanium(II) chlorides, [LPhGeCl] and [LMesGeCl]. Reactions of these, and the known complex, [L′GeCl] (L′ = −N(Ar*)(SiMe3)), with Na[CpMo(CO)3] have afforded the first examples of structurally characterized two-coordinate molybdenum substituted germylenes, [Cp(CO)3MoGeN(Ar*)(R)] (R = SiMe3 or Ph). The former readily eliminates a molecule of CO when heated or irradiated with UV light to give an unprecedented amino-germylyne complex, [Cp(CO)2Mo≡GeN(Ar*)(SiMe3)]. The spectroscopic and structural data for this complex, in combination with the results of computational studies, show that this compound is best viewed as having a bent Mo-Ge “triple” bond, with little multiple bond character to its Ge-N interaction. Computational studies have also indicated that the Mo-Ge-N bending in the complex is due to the extreme steric bulk of its amido substituent.
Gesehen am 07.05.2021
Publication Date: December 20, 2012